2012
DOI: 10.1007/s10043-012-0003-0
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing correlation effect using zero cross correlation code in spectral amplitude coding optical code division multiple access

Abstract: The use of minimal multiple access interference (MAI) in code design is investigated. Applying a projection and mapping techniques, a code that has a zero cross correlation (ZCC) between users in optical code division multiple access (OCDMA) is presented in this paper. The system is based on an incoherent light source -LED, spectral amplitude coding (SAC), and direct detection techniques at the receiver. Using power spectral density (PSD) function and Gaussian approximation, we obtain the signal-to-noise ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…, m is the mapping process [22]. As mentioned that a splitter is used to split one wavelength into N outputs and each n th output is modulated by 5Gbps then encoded by time delays to correlate the desired code.…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…, m is the mapping process [22]. As mentioned that a splitter is used to split one wavelength into N outputs and each n th output is modulated by 5Gbps then encoded by time delays to correlate the desired code.…”
Section: System Descriptionmentioning
confidence: 99%
“…In this paper, an optical CDMA-DWDM hybrid system with spacing 0.4nm is proposed to increase the capacity of the network and reduce the FWM effects. Zero cross correlation (ZCC) code is used as a signature sequence code, which has good properties in terms of auto and cross correlation [22]; hence the MAI can be reduced. On the other hand, the nonlinear effect of FWM, which degrades the signals in DWDM system, can be reduced by CDMA technology.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, using this code, the PIIN noise is eventually eliminated making it one of the best considered codes in the SAC OCDMA systems. In all previous work of ZCC [7][8][9], it was shown that the weight of the code words is similar and constant. In contrast, our interest is mainly focused on developing the variable weight ZCC for diversifying the code's applications such in the triple play services.…”
Section: Introductionmentioning
confidence: 98%
“…Many codes have been proposed based on SAC-OCDMA system such as MQC, MD, RD, etc, [4,5,6]. However, based on previously published papers at [7,8], ZCC code is considered the most recent and offers the highest code performance compared with other SAC codes. In this work, we propose a new technique known as hybrid optical OFDM/SAC-OCDMA based on SAC technique system.…”
Section: Introductionmentioning
confidence: 99%
“…The code structure does not have overlapping of bit ''1'' and it will not cause the ZCC code to interfere between users. The ZCC falls in a group of SAC codes and only shot noise and thermal noise have been considered, ignoring PIIN due to the zero cross correlation between users [9]. The newly proposed code can adapt to any variable number of weight and user without any constraint by using transformation and mapping technique respectively.…”
Section: Introductionmentioning
confidence: 99%